2014
DOI: 10.1002/2013jc009042
|View full text |Cite
|
Sign up to set email alerts
|

Observations and numerical modeling of the Pearl River plume in summer season

Abstract: A cruise survey of the Pearl River plume during southeasterly and southwesterly winds, two typical wind patterns in summer in Guangdong coastal waters, is reported and the cruise data are analyzed to unveil the plume dynamics. The Kelvin number is derived from the in situ data, revealing that the Pearl River plume exhibits two different scales in response to the two kinds of the wind forcing. Numerical model simulations based on the regional oceanic modeling system (ROMS) with nesting domains are implemented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…From Figure 6, we can see the plume water area is occupied by the downwelling-favorable wind. According to Pan et al (2014), the supercritical, distinct plume front is easily produced in the downwelling-favorable wind and spring tide. The front observed in the SAR image shall be a supercritical one.…”
Section: Asar Observationmentioning
confidence: 99%
See 2 more Smart Citations
“…From Figure 6, we can see the plume water area is occupied by the downwelling-favorable wind. According to Pan et al (2014), the supercritical, distinct plume front is easily produced in the downwelling-favorable wind and spring tide. The front observed in the SAR image shall be a supercritical one.…”
Section: Asar Observationmentioning
confidence: 99%
“…The pattern of the front suggests that the plume water was trapped by this front as a bulge lying near the river mouth. The bulge near the estuary mouth was observed by Pan et al (2014) using numerical model results. The bulge is formed under downwelling-favorable wind and strongly affected by the Earth's rotation as well as the momentum of the river discharge.…”
Section: Asar Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies confirm that the bulge is a naturally occurring phenomenon with many rivers (Chant et al, 2008;Horner-Devine et al, 2008;Horner-Devine, 2009;Valente and da Silva, 2009;Saldías et al, 2012;Hopkins et al, 2013;Mendes et al, 2014;Pan et al, 2014;Fernández-Nóvoa et al, 2015), but an anti-cyclonic rotation inside a bulge is observed seldom (Kudela et al, 2010;Horner-Devine, 2009;Chant et al, 2008). Observations of the evolution of the bulge over a certain time period are almost non-existent, with the ex-418 E. Soosaar et al: River bulge evolution and dynamics in a non-tidal sea ception of the Niagara River plume (Horner-Devine et al, 2008) and the Tagus estuary plume (Valente and da Silva, 2009).…”
Section: Introductionmentioning
confidence: 90%
“…On average, the influence of the canal on the coastal dynamics is small; however, sporadic, heavy rainfall events can force an outflow of freshwater into the coastal zone that alters the stratification. Although numerous modeling studies on large discharge rivers exist (Gracia Berdeal et al, 2002;Pan et al, 2014), the same is not true for rivers with small volume and aperiodic discharge.…”
Section: Introductionmentioning
confidence: 99%